Vibrational Spectrum of HMX at CO2 Laser Wavelengths: A Combined DRIFT and LPAS Study. (5th September 2012) - Puiu, A.; Giubileo, G.; Nunziante Cesaro, S.
Abstract : The vibrational spectrum of solid standard HMX (octahydro-1, 3, 5, 7-tetranitro-1, 3, 5, 7-tetrazocine) was investigated. Two spectroscopic techniques were adopted for their different sensitivity and resolution. A preliminary survey of the absorption bands of the compound was performed in the 8000–400 cm −1 spectral range by employing the diffuse reflectance infrared Fourier transform (DRIFT) technique at room temperature. The high-resolution line spectrum of HMX was obtained in the 9.2–10.8  μ m spectral range by laser photoacoustic spectroscopy (LPAS) method, using a line tuneable 10 W stabilised cw CO2 laser light source. By comparing the data collected with the two techniques in the common frequency range, a very good agreement was observed.